Perubahan Pengetahuan dan Sikap Remaja Putri terhadap Pencegahan Anemia melalui Media Aplikasi Berbasis Android di SMKN 9 Kota Padang - Muliana, Hanifah; Hayati, Neni Fitra; Sidiq, Rapitos; Novelasari, Novelasari; Amos, John; Doni, Alsri Windra (Jurnal Sehat Mandiri, 2023)
Anemia is a frequently encountered health issue in adolescent girls. The results of the Padang Pasir Health Center (2020) screening indicate that the highest risk of anemia occurred at SMKN 9 Padang City, reaching 26.31%. The research aims to determine changes in the knowledge and attitudes of adolescent girls towards preventing anemia through an android-based application at SMK Negeri 9 Padang City. This study used a mixed methods approach, using a qualitative exploratory case study and a quasi-quantitative experimental design with one group pretest-posttest setting. The research population consisted of 274 grade 11 students at SMKN 9 Padang City with a total sample of 73 students. Qualitative data was collected through an interview guide, while quantitative data was collected using a pretest-posttest questionnaire. The results of qualitative research in making Android-based applications, and quantitative results show an average increase in knowledge scores from 11.04 to 15.56, and attitude scores from 51.41 to 60.37 after attending education using Android-based applications. This shows a significant increase in knowledge and attitude with a p-value of 0.0001 (p<0.05). In conclusion, there was a change in knowledge and attitude before and after counseling through an android-based application about preventing anemia in young women at SMK Negeri 9 Padang City. Future researchers are encouraged to develop more comprehensive content and a variety of features to expand the range of Android-based applications.